Pengabdian Masyarakat : Sosialisasi Kurikulum Merdeka di SD Negeri 2 Bayem - Nugroho, Yusuf Arieffudin; Rachmawati, Amira Yuniar; Evoni, Anggita Fitri; Lestari, Putri Ayu (JRCE (Journal of Research on Community Engagement), 2023)
This research aims to describe the obstacles experienced by elementary school teachers in implementing the Merdeka Curriculum on the background of observation data showing the acquisition of student learning outcomes at SD Negeri 2 Bayem in implementing the independent curriculum. To respond to this, the researcher conducted class action research that aimed to improve the results of students' learning activities. The objective to be achieved in this study is to analyze the ability of students obtained using the independent curriculum.The implementation of this research covers all classes where the implementation of the independent curriculum at SD Negeri 2 Bayem is not entirely implemented. This Merdeka Curriculum is only applied in grades 4, 5, and 6 with a total of 30 students per class while grades 1, 2, and 3 have not fully used this independent curriculum because the teachers at SD Negeri 2 Bayem still have not fully mastered the independent curriculum and the obstacles include the age of the teachers and the limitations in running social media which are lacking.